I was Jane Austen's best friend - Harrison, Cora (New York, NY. : Scholastic, 2010)
In a series of journal entries, Jenny Cooper describes her stay with cousin Jane Austen in the 1790s, and her entrance into Jane's world of beautiful dresses, dances, secrets, gossip, and romance.